Computer-aided design of dental inlay restoration based on dual-factor constrained deformation. (December 2017) - Zhang, Changdong; Liu, Tingting; Liao, Wenhe; Yang, Tao; Jiang, Liyi
Highlights: This approach propose an entire framework for modeling inlays that involves cavity contour extraction, tooth positioning, tooth surface segmentation and occlusal surface deformation, which cover almost all important modeling steps for the digital design of inlays. Combined with analyzing the feature information of the residual tooth cavity based on the local surface fitting method and exploring the shortest path problem in graph theory, a smooth cavity contour is extracted by a heuristic searching algorithm. This paper provides a semi-automatic template tooth positioning method for tooth surface segmentation that is more efficient than traditional interactive manipulation. Compared with current methods for occlusal surface reconstruction, this paper introduces a dual-factor constrained deformation strategy by defining a segmentation constraint and cavity contour constraint. This strategy is subsequently robust and efficient in clinical application, thus providing an adaptive and robust modeling tool for high-quality occlusal surface reconstruction. Abstract: Computer-aided design technology has been applied extensively in the field of dental restoration. Inlay is a commonly used restoration type for reconstructing the partially destroyed teeth and restoring occlusal function. The designed occlusal surface should fit the anatomy of each defect region, and the modeling process should be efficient for clinical applications. This paper presents a robust dual-factor constrained deformation framework for dental inlay modeling, consisting of four necessary steps: cavity contour extraction using a heuristic search strategy, semi-automatic template tooth positioning through a four-step affine transformation involving ``Translation-Rotation-Rotation-Scaling", tooth surface segmentation by means of sampling ray-tracing collisions, and occlusal surface reconstruction based on dual-factor constrained deformation, which was implemented by defining a segmentation constraint and cavity contour constraint. We demonstrate the effectiveness and robustness of the proposed method by presenting several clinical applications. The designed 3D inlay model can retain the morphological features of generic teeth and match well with the residual tooth surface.